2022
DOI: 10.1210/endocr/bqac169
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Glycogen Metabolism Induces Reactive Oxygen Species-Dependent Cytotoxicity in Anaplastic Thyroid Cancer in Female Mice

Abstract: Anaplastic thyroid cancer (ATC) is one of the most lethal solid tumors, yet there are no effective, long-lasting treatments for ATC patients. Most tumors, including tumors of the endocrine system, exhibit an increased consumption of glucose to fuel cancer progression, and some cancers meet this high glucose requirement by metabolizing glycogen. Our goal was to determine if ATC cells metabolize glycogen and if this could be exploited for treatment. We detected glycogen synthase and glycogen phosphorylase (PYG) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 60 publications
0
3
0
Order By: Relevance
“…Further research is needed to understand certain elements of the relationship between the regulation of glycogen degradation and the hepatocellular intraluminal redox state. In addition, glycogen metabolism has recently become one of the targets of antitumor therapy [ 53 ]. One explanation for this is the relationship between glycogen metabolism and redox homeostasis.…”
Section: Discussionmentioning
confidence: 99%
“…Further research is needed to understand certain elements of the relationship between the regulation of glycogen degradation and the hepatocellular intraluminal redox state. In addition, glycogen metabolism has recently become one of the targets of antitumor therapy [ 53 ]. One explanation for this is the relationship between glycogen metabolism and redox homeostasis.…”
Section: Discussionmentioning
confidence: 99%
“…Several clinical studies have reported monotherapy with a multi-tyrosine kinase inhibitor is not recommended for mild effects in patients with ATC [ 66 , 67 ]. Recently, many investigations have shown combination treatment with these drugs is more effective than drug monotherapy for ATC [ 68 71 ]. We also showed co-inhibition of glutamine and one-carbon metabolism increased the efficacy of lenvatinib and sorafenib.…”
Section: Discussionmentioning
confidence: 99%
“…For example, kinase inhibitors dasatinib and trametinib were shown to alter metabolic flux in anaplastic and papillary thyroid cancer cells [ 45 ]. In anaplastic thyroid cells in mice, targeting glycogen metabolism by inhibiting glycogen phosphorylase resulted in increased glucose flux, impairment of PPP, reactive oxygen species accumulation, and eventual cytotoxicity [ 46 ].…”
Section: Metabolism In Thyroid and Other Cancersmentioning
confidence: 99%